Phage display as a tool for synthetic biology - Carnazza, Santina (Nanotechnology science and technology series., 2010)
Phage display can be considered as a practical realization of an artificial chemical evolution. As such, it is an useful tool for in vitro protein evolution, aimed to identifying new receptors and natural ligands for "orphan receptors", drug discovery (peptides might act as enzyme inhibitors and receptor agonists or antagonists, or otherwise modulate the enzyme/receptor's biological effect), "epitope discovery" (a new approach to disease diagnosis and vaccine development), design of DNA-binding proteins, source of new materials, antibody phage and recombinant phage probes, next-generation nano-electronics, targeted therapy, molecular imaging, gene delivery and phage-display vaccination. All this can be regarded as a kind of synthetic biology in that it involves the reshaping and redirecting of natural molecular systems, phage, typically using the tools of protein and genetic engineering.--Provided by publisher.